The canning of chinese waterchesnuts (Eleocharis tuberosa schult) in brine - Pineda, Alicia S.; De Leon, Sonia Y. (1973.)
The srudy was on the standardization of the formulation and procedure of preparing glass-packed Chinese waterchestnuts in brine. Product processed in the laboratory was evaluated with a commercial product. Determination of the optimum processing time was based on heat penetration studies, microbiological tests, and subjective evaluation. The choice for the optimum brine concentration was based on panel evaluation. Comparative evalutaion was conducted using physico-chemical tests and sensory evaluation in terms of the product's quality and acceptability. results of the various tests indicated that waterchestnuts packed in 3% brine and processed for 10 minutes at 250°F can compare in quality and acceptability with a local commercial brand of of canned waterchestnuts. Limitations, problems and recommended further studues cited in the research included specifications on the maturity stage of the product, peeling methods, and the leuco-anthocyanin pigments which may account for the observed pink and grayish discoloration in waterchestnuts.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Eleocharis dulcis -- Canning of